A framework for quality measurement in the presurgical care of chronic rhinosinusitis: a review from the Quality Improvement Committee of the American Rhinologic Society. Issue 12 (3rd September 2018) - Mattos, Jose L.; Soler, Zachary M.; Rudmik, Luke; Manes, Peter R.; Higgins, Thomas S.; Lee, Jivianne; Schneider, John; Setzen, Michael; Parasher, Arjun K.; Smith, Timothy L.; Stokken, Janalee K.
Abstract : Background: Quality improvement (QI) in the management of chronic rhinosinusitis (CRS) is garnering increasing attention. Defining frameworks and metrics to assess the quality of key components in CRS management could assist in reducing unwarranted practice variation and increase high‐quality care. Methods: A panel of the American Rhinologic Society (ARS) QI committee reviewed the literature to determine important presurgical components of CRS care that warrant QI. The evidence was organized into 4 categories: (1) diagnosis, (2) medical management, (3) appropriate patient selection for surgery, and (4) patient‐centered discussion. The combination of these categories was used to develop a framework termed the CRS Appropriate Presurgical Algorithm (CAPA). Results: Prior to offering surgery for CRS, the best available evidence support the following quality metrics: (1) a guideline‐based diagnosis should be confirmed; (2) appropriate medical management, including a minimum of topical corticosteroid therapy and saline irrigations, should have been attempted (assuming patient tolerance); (3) a computed tomography (CT) scan should be obtained (to confirm the presence of sinus inflammation and for surgical planning); and (4) a patient‐centered discussion regarding treatment options for refractory CRS (ie, alternative medical therapies vs surgery vs observation) while focusing on risks and benefits, the need for long‐term medical compliance, and understanding of patient preferences and expectations. Conclusion: Defining metrics that assess key components to CRS care prior to offering surgery has the potential to further improve upon an already successful treatment paradigm, reduce unwarranted practice variation, and to ensure that patients are receiving a similar level of high‐quality care.